2003
DOI: 10.5694/j.1326-5377.2003.tb05660.x
|View full text |Cite
|
Sign up to set email alerts
|

Badmouthing GPs

Abstract: The recent issue on general practice (7 July 2003) contained many statements that were inaccurate and unfair to a profession that has existed before most specialties and will exist beyond their passing. It is unfortunate that the issue represents an opportunity missed.Notwithstanding the funding issues, general practice is not "in crisis", as many of your authors would attest. 1 It is vibrant and leading the way in healthcare reform in this country, and much of its loss of appeal to new doctors has to do with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Studies in the field of undergraduate education have shown that “badmouthing” of family medicine negatively influences students in their career choice [5, 15, 16]. “Badmouthing” is defined as “unjustified, negative, and slanderous comments by physicians about other physicians in various branches of medicine” [15].…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the field of undergraduate education have shown that “badmouthing” of family medicine negatively influences students in their career choice [5, 15, 16]. “Badmouthing” is defined as “unjustified, negative, and slanderous comments by physicians about other physicians in various branches of medicine” [15].…”
Section: Discussionmentioning
confidence: 99%